2022
DOI: 10.3390/jcm11216486
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Antihypertensive Drugs on Cardiovascular Risk in Isolated Systolic Hypertension with Type 2 Diabetes Patients

Abstract: Backgrounds: Angiotensin receptor blockers (ARB), angiotensin converting enzyme inhibitor (ACEI), calcium channel blocker (CCB) and thiazide diuretics (TD) are common antihypertensive drugs for diabetes patients with hypertension. The purpose of this study was to compare the cardiovascular risks of these drugs in patients with isolated systolic hypertension (ISH) and type 2 diabetes mellitus (T2DM). Methods: We used Action to Control Cardiovascular Risk in Diabetes trial data to explore the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…As antihypertensive agents, the results of this study showed an acceptable blood lowering effects for both, ARBs and CCBs, with more potent action from ARBs in comparison to CCBs. This is in consistence with the previous researches, where both groups have been used for controlling BP in diabetic patients and that ARBs are superior to all other classes (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…As antihypertensive agents, the results of this study showed an acceptable blood lowering effects for both, ARBs and CCBs, with more potent action from ARBs in comparison to CCBs. This is in consistence with the previous researches, where both groups have been used for controlling BP in diabetic patients and that ARBs are superior to all other classes (15,16).…”
Section: Discussionsupporting
confidence: 90%
“… 3 In a prior analysis of ACCORD‐BP, Gao et al observed that participants who were prevalent users of ARBs at baseline experienced lower rates of the primary outcome during the trial, but did not observe the same relationship with ACEIs, calcium channel blockers, or thiazide diuretics. 27 However, this analysis is subject to prevalent user bias, and the results should be interpreted with great caution. The current American College of Cardiology/American Heart Association and the European Society of Cardiology/European Society of Hypertension BP guidelines recommend both classes interchangeably, 1 , 28 and there may be further evidence that ARBs provide more protection against hypertension‐mediated cognitive decline and cancer outcomes.…”
Section: Discussionmentioning
confidence: 98%